Intraoperative loading of calcium phosphate-coated implants with gentamicin prevents experimental Staphylococcus aureus infection in vivo. - Keith Thompson (PLoS ONE, 2019)
Orthopedic device-related infection (ODRI) is a potentially devastating complication arising from the colonization of the device with bacteria, such as Staphylococcus aureus. The aim of this study was to determine if intraoperative loading of a clinically approved calcium phosphate (CaP) coating with gentamicin can protect from ODRI in vivo. First, CaP-coated titanium aluminium niobium (TAN) discs were used to investigate the adsorption and release kinetics of gentamicin in vitro. Gentamicin loading and subsequent release from the coating were both rapid, with maximum loading occurring following one second of immersion, and >95% gentamicin released within 15 min in aqueous solution, respectively. Second, efficacy of the gentamicin-loaded CaP coating for preventing ODRI in vivo was investigated using a CaP-coated unicortical TAN screw implanted into the proximal tibia of skeletally mature female Wistar rats, following inoculation of the implant site with S. aureus. Gentamicin-loading prevented ODRI in 7/8 animals, whereas 9/9 of the non-gentamicin treated animals were infected after 7 days. In conclusion, gentamicin can be rapidly and simply loaded onto, and released from, CaP-based implant coatings, and this is an effective strategy for preventing peri-operative S. aureus-induced ODRI in vivo.